Multiple-Beams Splitter Based on Graphene - Xiao Bing Li; Hong Ju Xu; Wei Bing Lu; Jian Wang (International Journal of Optics)
Due to its tunability of conductivity, graphene can be considered as a novel epsilon-near-zero (ENZ) material. Based on this property, we propose a wave splitter using graphene. Simulation results show that the circular surface plasmon polariton waves excited by a point source can be transferred to narrow beams through a graphene-based wave splitter, which is formed by a polygonal contour of the ENZ graphene layer. The number of beams can be easily controlled by adjusting the shape of the polygonal ENZ graphene layer, and the operation frequency can also be chosen.